Digestive ripening: a fine chemical machining process on the nanoscale - Shimpi, Jayesh Ramesh; Sidhaye, Deepti S.; Prasad, Bhagavatula L V (Langmuir, 2017)
A comprehensive over view of the process named as 'digestive ripening' that is known to convert polydisperse nanocrystals to monodisperse ones is presented. Apart from highlighting the role of organic molecules (ligands) in achieving size control the role of other parameters like the nanocrystal-ligand binding strength and the temperature at which the reaction is carried out in accomplishing size control is also delineated. The generality of the procedure is illustrated by providing examples of how it is used to prepare monodispersed nanocrystals of different metals, alloy systems, ultra small nanocrystals and also to narrow the size distribution in complex binary and ternary nanocrystal systems. Finally, the current status as far as the theoretical understanding of how the size control is being achieved by digestive ripening is laid out, emphasizing at the same time the necessity to undertake more systematic studies to completely realize the full potential of this practically very useful procedure.